Virtual Da’wah on TikTok: A Virtual Ethnography of @Munawar.Rifadi - Muhammad Saepul Ulum; Nabila Syahidah Nurmahabbatullah (Feedback International Journal of Communication, 2026)
Religious education is undergoing a significant transformation driven by social media logic. This study explores the digital da’wah strategies of Munawar Rifadi on TikTok, focusing on how he addresses the 65% Quranic illiteracy rate among Indonesian Muslims through innovative pedagogy. Using a virtual ethnographic approach and Cyber Media Analysis (CMA) framework, the researcher observed content artifacts, interactive Live sessions, and community engagement patterns over a specific sampling period. The findings identify four strategic pillars namely Literacy Advocacy, Interactive Virtual Classrooms, Technical Mnemonics (the Marhalah Method), and Radical Inclusivity. The study reveals that the creator successfully remediates the da’wah bil hikmah principle by simplifying complex Arabic phonetics into snackable vertical video content. Discussion through the lens of Mediatization and Networked Authority suggests that religious credibility is now negotiated through interactivity and functional utility rather than traditional hierarchy alone. The Media Space of TikTok is effectively repurposed into a decentralized Halaqah, where digital interactions foster offline spiritual consistency. This research concludes that @Munawar.Rifadi’s model democratizes religious learning and dismantles social stigmas for adult learners. However, the study is limited by its qualitative focus on a single creator. Future research should employ mixed-methods to quantify long-term behavioral changes and engagement efficacy across broader demographics in the digital ummah.